2018
DOI: 10.1021/acs.energyfuels.8b01824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbonaceous Precursors on the Structure of Mesophase Pitches and Their Derived Cokes

Abstract: Using six representative feedstocks as carbonaceous precursors, various mesophase pitches and their derived cokes were obtained by a heat-soaking method at a temperature range of 400−450 °C and a pyrolysis treatment at 900 °C, respectively. The optical texture and microstructure of the different mesophase pitches and their derived cokes were characterized by polarized-light microscope, scanning electron microscope, and X-ray diffraction. The results show that the formation and development abilities of liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
(72 reference statements)
0
20
0
Order By: Relevance
“…Figure 3 shows the flow diagram of catalytic thermal polymerization of naphthalene molecule to prepare carbonaceous mesophase pitch as shown in Figure 2(b) by a two-step reaction process at a liquid-phase carbonization temperature of 350-450°C for a certain period of time. It could be concluded that some carbonaceous precursors (e.g., naphthalene) have undergone four stages of liquid-crystalline sphere development and transformation and finally formed a bulk liquid-crystalline mesophase from an isotropic matrix as illustrated in Figure 4 under a suitable reaction condition (i.e., reaction temperature and time) [2,15,16]. The general four-stage conversion of liquid crystals during the whole process is diagramed as follows: (I) generation of optically anisotropic spheres in isotropic matrix, (II) growth of anisotropic spheres in isotropic matrix, (III) coalescence of anisotropic spheres in isotropic matrix, and (IV) deformation and disintegration of anisotropic coalesced spheres to form bulk liquid-crystalline mesophase.…”
Section: Preparation Of Carbonaceous Mesophasementioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3 shows the flow diagram of catalytic thermal polymerization of naphthalene molecule to prepare carbonaceous mesophase pitch as shown in Figure 2(b) by a two-step reaction process at a liquid-phase carbonization temperature of 350-450°C for a certain period of time. It could be concluded that some carbonaceous precursors (e.g., naphthalene) have undergone four stages of liquid-crystalline sphere development and transformation and finally formed a bulk liquid-crystalline mesophase from an isotropic matrix as illustrated in Figure 4 under a suitable reaction condition (i.e., reaction temperature and time) [2,15,16]. The general four-stage conversion of liquid crystals during the whole process is diagramed as follows: (I) generation of optically anisotropic spheres in isotropic matrix, (II) growth of anisotropic spheres in isotropic matrix, (III) coalescence of anisotropic spheres in isotropic matrix, and (IV) deformation and disintegration of anisotropic coalesced spheres to form bulk liquid-crystalline mesophase.…”
Section: Preparation Of Carbonaceous Mesophasementioning
confidence: 99%
“…However, it has been demonstrated that the formation, development, and transformation of liquid-crystalline anisotropic spheres (i.e., nucleation, growth, coalescence and deformation and orientation) in an isotropic pitch matrix are unconcerted and inhomogeneous during the process of liquid-phase carbonization as shown in Figure 5 [16]. Furthermore, it is not easy to obtain a 100 vol.% anisotropic mesophase pitch (i.e., bulk mesophase) both with a fine flow optical texture and an acceptable softening point less than 300°C for subsequent fiber spinning.…”
Section: Preparation Of Carbonaceous Mesophasementioning
confidence: 99%
See 2 more Smart Citations
“…As a type of polycyclic aromatic carbonaceous compounds with excellent physical and chemical properties, coal pitch has attracted more attention in varied fields such as: metallurgy, the chemical industry, machining, and construction 1–4 . In recent years, the efficient and high value‐added utilization of coal pitch has been a common research topic 5–8 . Coal pitch is usually divided into four categories in literature: high‐temperature coal tar pitch, 9 medium‐low‐temperature pitch, 10 coal liquefied pitch, 11 and synthesized pitch 12,13 …”
Section: Introductionmentioning
confidence: 99%